Use of physical exertion to enhance objective testing following mild traumatic brain injury: a systematic review - Duncan Reid; Katherine Forch; Sharon Olsen; Mangor Pedersen; Nicola CM Towersey (BMJ Open Sport & Exercise Medicine)
Background Assessment of recovery from mild traumatic brain injury (mTBI) is complex and challenging. Post-exertion testing, where individuals undergo objective testing following physical exercise, has shown promise in identifying mTBI-related impairments that may not be evident at rest, but could hinder a safe return to sport.Objectives To conduct a systematic review to determine if physical exertion affects objective physiological or sensorimotor tests differently in individuals with mTBI compared with healthy controls.Methods A systematic search of 11 databases and five trial registries on 30 May 2024 identified reports that: (i) compared individuals aged 12–65 years within 12 months of mTBI against healthy control participants, (ii) investigated the effects of a single session of physical exertion and (iii) collected before, during or after exertion, objective measures of physiological or sensorimotor function. Risk of bias was assessed with the Risk Of Bias In Non-randomized Studies of Interventions tool. Results were analysed descriptively.Results The review included 22 studies with 536 participants wih mTBI. Risk of bias was deemed high. At rest, 8/22 (36%) studies detected differences in physiological responses between participants wih mTBI and healthy control participants. During or after exertion, 21/22 (96%) studies detected differences in physiological responses, including cardiovascular, respiratory and cerebral autoregulation.Conclusion The findings indicate that objective testing during or after physical exertion can enhance the ability to detect mTBI-related impairments in various physiological parameters, and this concept could be considered when monitoring recovery and return to sport. Further studies are needed.PROSPERO registration number CRD42023411681.